Applying kagan cooperative learning structures to improve 11th grade students’ speaking skills at a high school in Thai Binh - Phạm, Thị Nhung (2020)
The main objective of learning English is using English as a means of communication. To achieve that objective, teachers can use appropriate techniques which match with the learners’ characteristics in teaching speaking. Kagan cooperative learning structures (KCLS), a student-centered instructional approach, is believed to have the potential to encourage more interactions among students and maximize the improvement of each student’s learning process, thus have good effect on teaching in classroom. That is the reason why in this action research project, KCLS was applied in the speaking lessons of a grade 11 class at a high school in Thai Binh with a view to improving the students’ speaking skills. The findings from the data collected via questionnaire, teacher’ journals and speaking test scores showed great improvement in students’ speaking skills both in linguistic and paralinguistic features. The students also have positive attitudes toward the use of KCLS in class. This project provides recommendations to English teachers for implementing a cooperative learning approach when teaching of English speaking skills in the context of high school in Vietnam.